2012
DOI: 10.1097/ede.0b013e31823a44a5
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Influenza H1N1

Abstract: The difference between age-groups may help to explain high estimates of the reproduction number from outbreaks involving a large proportion of child cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 73 publications
1
6
0
1
Order By: Relevance
“…Using the excess degree of children and adults, the age specific R 0 can be estimated for both children and adults. We showed that R 0 for children is higher than that for adults (1.28 versus 1.08), which is consistent with other studies (see [19]). This implies that school-aged children likely contributed more infections than adults.…”
Section: 9supporting
confidence: 93%
“…Using the excess degree of children and adults, the age specific R 0 can be estimated for both children and adults. We showed that R 0 for children is higher than that for adults (1.28 versus 1.08), which is consistent with other studies (see [19]). This implies that school-aged children likely contributed more infections than adults.…”
Section: 9supporting
confidence: 93%
“…Children are of particular importance due to the high attack rate among them and their known role in dispersing of the disease. This was indeed proven for the A(H1N1)pdm09 virus by Glass et al 26. These thresholds are important for policy makers to set minimum targets for vaccination coverage for novel influenza strain, as well as seasonal viruses.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, the completeness of the data could be affected by underreporting as some of the parents might have regarded measles as a kind of skin disease or might have confused it with other diseases that involve skin rashes. Apart from that, age-specific Rs are common to be used as a metric to identify appropriate age groups most responsible for transmission as for a target of interventions [10,12,13]. However, when determining the effort required to eliminate an infection, the interpretation of an age-specific R is different from that of an overall R in a heterogeneous population as using the original threshold of unity could lead to an underestimation of target population for interventions [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some infectious diseases have been shown to be strongly age-specific, for example, measles. Age-specific R, defined as an average total number of secondary cases from all age groups generated by a single case with respect to his age group was recommended to study the differences in transmission potential taking account of social mixing [10][11][12][13][14][15]. Although a usual interpretation of age-specific R for gauging the control measures required to eliminate an infection is inappropriate [16,17], age-specific Rs provide valuable information on the underlying heterogeneous transmission between and within different groups of individuals.…”
Section: Introductionmentioning
confidence: 99%